Ecological Significance of Laser Leveling of Lands. - A.M.Abdulloyev; A.B.Ochilov; A.B.To’xtamishov (Indonesian Journal of Innovation Studies, 2022)
The economic efficiency of laser leveling of lands is that in Uzbekistan the cultivation of agricultural crops is based on irrigated agriculture, where 90-95% of the crop is grown. Caring and cultivation of crops is carried out by applying several agro-technical measures, the most important of which is land leveling. In agriculture, the main purpose of land leveling is to carry out irrigation and mechanized agro-technical measures while maintaining the slope of the field.